Jazz diplomacy : promoting America in the Cold War era - Davenport, Lisa E. (American made music series, 2009)
Jazz as an instrument of global diplomacy transformed superpower relations in the Cold War era and reshaped democracy's image worldwide. Lisa E. Davenport tells the story of America's program of jazz diplomacy practiced in the Soviet Union and other regions of the world from 1954 to 1968. Jazz music and jazz musicians seemed an ideal card to play in diminishing the credibility and appeal of Soviet communism in the Eastern bloc and beyond. Government-funded musical junkets by such jazz masters as Louis Armstrong, Dave Brubeck, Duke Ellington, Dizzy Gillespie, and Benny Goodman dramatically influenced perceptions of the U.S. and its capitalist brand of democracy while easing political tensions in the midst of critical Cold War crises. This book shows how, when coping with foreign questions about desegregation, the dispute over the Berlin Wall, the Cuban missile crisis, Vietnam, and the Soviet invasion of Czechoslovakia, jazz players and their handlers wrestled with the inequalities of race and the emergence of class conflict while promoting America in a global context. And, as jazz musicians are wont to do, many of these ambassadors riffed off script when the opportunity arose.